Gamification in E-Learning: Transforming Education through Technology - Domingo, Marianne Faith; Bautista, Carlo Andrew; Fajardo, Alyssa Jean (International Journal of Technology and Modeling, 2025)
The integration of gamification into e-learning has become a transformative force in education, particularly in developing countries such as the Philippines. This study explores the impact of gamified e-learning platforms on student engagement and academic performance in higher education institutions in the Philippines. Using a mixed-methods approach, data were collected from 150 undergraduate students across three universities through surveys, interviews, and academic performance records. The results show that 82% of participants reported increased motivation and engagement when using gamified learning platforms, and 67% demonstrated improved academic performance compared to those using traditional e-learning methods. Students particularly responded positively to elements such as badges, leaderboards, and point-based systems, which enhanced their sense of competition and achievement. Despite some challenges in implementation—such as internet accessibility and the need for culturally relevant game design—the study concludes that gamification holds significant potential to improve the effectiveness of e-learning in the Philippine educational context.